Perlindungan Hukum Atas Pencabutan Izin Usaha Pertambangan Oleh Satuan Tugas Penataan Penggunaan Lahan dan Penataan Investasi - Gultom, Devi Roma Loisa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The protection of law-abiding mining permit holders whose IUP (Mining Business Permit) is revoked by the Minister of BKPM (Investment Coordinating Board) is the topic addressed in this article. This article aims to identify and analyze the legal basis for the revocation of IUPs by the Minister of BKPM, as well as the legal protection available to affected IUP holders. The research method used in this case study is a normative juridical approach. The author examines and studies data including primary, secondary, and tertiary legal materials, as well as bibliographic data. The research findings indicate that the revocation of IUPs is a last resort measure for administrative sanctions for companies failing to meet their obligations, and that the revocation carried out by the BKPM Task Force is legally flawed and violates the provisions of Article 188 of Government Regulation No. 96/2021. Legal protection available to affected permit holders includes administrative legal remedies, requests, and administrative court lawsuits.